GENDER INEQUALITY ANALYSIS IN THEODORE DREISER’S SISTER CARRIE - Fahreza, Mas Andika; Risnawaty, Risnawaty (PHILOLOGY Journal of English Language and Literature, 2025)
This research aims to analyze gender inequality in Theodore Dreiser's Sister Carrie (1900), focusing on the intersection of social structure and economic inequality. Using a qualitative research method, as outlined by Creswell (2013), this study examines the ways in which gender roles and social class disparities shape the lives and experiences of the novel's central characters. The theoretical framework draws upon Fakih’s (2013) perspective on gender inequality, which highlights the systemic nature of gender-based oppression within social and economic structures. Through a close reading of Sister Carrie, the research explores how Carrie Meeber’s social mobility and relationships are impacted by her gender, as well as how economic systems reinforce her position as a marginalized woman. The analysis reveals the intricate ways in which gender inequality is intertwined with class structures and economic forces, influencing the choices and agency of female characters in a capitalist society. This study contributes to understanding the role of gender and economic inequality in early 20th-century American literature, shedding light on the enduring relevance of these issues in contemporary society.